2023
DOI: 10.1021/acs.bioconjchem.2c00601
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Modular NTA:His Tag Viral Vaccine for Co-delivery of Antigen and Adjuvant

Abstract: The SARS-CoV-2 pandemic has highlighted the need for vaccines that are effective, but quickly produced. Of note, vaccines with plug-and-play capabilities that codeliver antigen and adjuvant to the same cell have shown remarkable success. Our approach of utilizing a nitrilotriacetic acid (NTA) histidine (His)-tag chemistry with viral adjuvants incorporates both of these characteristics: plug-and-play and co-delivery. We specifically utilize the cowpea mosaic virus (CPMV) and the virus-like particles from bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…The immunization with CPMV/Qβ-S100A9 elicited high antibody titers. The viral nanoparticles (VNPs) act as a carrier and adjuvant, and recent research highlights that in particular, conjugation results in codelivery of the epitope and adjuvant to the same cell boosting the potency of antibody production ( 52 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…The immunization with CPMV/Qβ-S100A9 elicited high antibody titers. The viral nanoparticles (VNPs) act as a carrier and adjuvant, and recent research highlights that in particular, conjugation results in codelivery of the epitope and adjuvant to the same cell boosting the potency of antibody production ( 52 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…To surmount these limitations, they have successfully loaded bacteriophage nanoplatforms. For example, the linkage of 2-methoxyethoxy-8-oxo-9-(4-carboxybenzyl) adenine (1V209) as TLR7 agonist on Qβ has reduced tumor growth in vivo and has extended the survival of mice in comparison to those treated with free 1V209 [165]. To this end, Bachmann et al have demonstrated the incorporation of CpG oligodeoxynucleotide (ODN) into Qβ, which serve as carriers [69].…”
Section: Phage-based Anticancer Vaccines Deliverymentioning
confidence: 99%
“…2c). 48 In vivo studies revealed that compared with free agonists or simple mixtures of agonists and VLPs, agonist chemically conjugated to VLPs elicited higher production of inflammatory cytokines, Apart from viruses derived from plant sources, the protein capsid of bacteriophages infecting bacteria has been established as a self-assembly VLP antigen-loading platform. In addition to the bacteriophage Qβ VLPs mentioned above, the P22 VLP derived from the Salmonella typhimurium bacteriophage P22 is considered a versatile VLP platform owing to its outstanding stability, modifiability, and facile heterologous expression.…”
Section: Vlpsmentioning
confidence: 99%
“…[45][46][47] (2) Immune adjuvants: PNPs can carry adjuvants like CpG through covalent interaction and other methods, further activating APCs by means of promoting the maturation of dendritic cells (DCs) and the polarization of tumor-associated macrophage (TAM) into the tumor-suppressing M1 phenotype, also releasing inflammatory cytokines to reverse the immunosuppressive tumor microenvironment. [48][49][50] (3) Drugs/photosensitizers/photothermal agents: due to the hydrophobic interactions of proteins like albumin and the pHresponsive characteristic of ferritin, various cargoes can be loaded into PNPs. For example, loading with chemotherapeutic drugs such as doxorubicin (DOX) and paclitaxel can induce ICD and enhance anti-tumor immune responses, or loading with photosensitizers/photothermal agents for photodynamic therapy (PDT)/photothermal therapy (PTT) also can induce ICD or generate reactive oxygen species (ROS) capable of directly killing cancer cells.…”
Section: Introductionmentioning
confidence: 99%